Two-Year Change in Serum Total Cholesterol Is Associated With Incident Ischemic Stroke: Results From the Kailuan Study - Wang, Yu; Wang, Anxin; Zuo, Yingting; Wu, Shouling; Zhao, Xingquan (Frontiers in Neurology, 2021)
Background and purpose: Compared with one single measurement, dynamic change of lipid parameter calculated by repeated measurements has been recognized as a potential biometric to make stroke risk assessments. Total cholesterol (TC) is an important risk factor for stroke, but the relationship between TC change and incident stroke has not been investigated thoroughly. We thus aimed to explore the association between two-year TC change and the risk of incident stroke, both ischemic and hemorrhagic, in the general population. Methods: From June 2006 to October 2007, a total of 70,999 participants with complete TC value at baseline (2006-2007) and the second examination (2008-2009) were included in our study. The change of TC was calculated as the two-year follow-up TC subtracting baseline TC. Cox proportional hazards regression analysis was used to evaluate the association between the tertile of TC change and risk of incident stroke and stroke subtypes. Results: 2,815 cases of stroke events were identified with a median follow-up period of 9.0 years. After adjusting for baseline TC and confounding factors, two-year TC change was independently associated with increased risk of total stroke (HR 1.07, 95% CI 1.02-1.12) and ischemic stroke (HR 1.08, 95% CI 1.03-1.13) for per SD (1.04 mmol/L) increase. While no significant association was obtained between TC change and intracerebral hemorrhage (p=0.659). Conclusions: Increased two-year TC change is associated with an elevated risk of incident total stroke and ischemic stroke, irrespective of the baseline TC value. Maintaining a sustained ideal level of TC is important for stroke prevention.